2000
DOI: 10.2307/3246584
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and environment of a New Zealand raised bog

Abstract: Abstract. The vegetation of a mire in a medium‐high rainfall area of South Island, New Zealand is described. The central part of the bog is raised 6 m above the surroundings, suggesting that it is ombrotrophic, and the species present are those of apparently ombrotrophic bogs elsewhere in New Zealand. pH of < 4.0 and Ca/Mg molar quotient of < 1.0 also indicates ombrotrophic conditions. Within the mire, these criteria provide effective discrimination between the fen (rheotrophic) and bog (ombrotrophic) communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There mire-like vegetation lacking cushions, such as Carex-Gentianella mire (H) occurs. Cushions are well known from blanket mires in the subalpine zone of the South Island, New Zealand (Burrows 1969;Burrows & Dobson 1972;Johnson et al 1977;Lough et al 1987;Mark & Wilson 2005), and they are also important in domed mires (McQueen & Wilson 2000). Gaimardia setacea (Centrolepidaceae), Oreobolus pectinatus (Cyperaceae), and Donatia novae-zelandiae (Donatiaceae) are the most common cushions in the Lammerlaw mires, tending to occur in the better-drained communities at the margins or base of the mires (J, Celmisia-Gentianella-Sphagnum mire base; N, Donatia herbfield; R, Oreobolus cushion mire; S, Gaimardia mire).…”
Section: Mire Vegetationmentioning
confidence: 99%
See 2 more Smart Citations
“…There mire-like vegetation lacking cushions, such as Carex-Gentianella mire (H) occurs. Cushions are well known from blanket mires in the subalpine zone of the South Island, New Zealand (Burrows 1969;Burrows & Dobson 1972;Johnson et al 1977;Lough et al 1987;Mark & Wilson 2005), and they are also important in domed mires (McQueen & Wilson 2000). Gaimardia setacea (Centrolepidaceae), Oreobolus pectinatus (Cyperaceae), and Donatia novae-zelandiae (Donatiaceae) are the most common cushions in the Lammerlaw mires, tending to occur in the better-drained communities at the margins or base of the mires (J, Celmisia-Gentianella-Sphagnum mire base; N, Donatia herbfield; R, Oreobolus cushion mire; S, Gaimardia mire).…”
Section: Mire Vegetationmentioning
confidence: 99%
“…In New Zealand this species is widespread in such environments (Burrows 1969;Dobson 1977;Mark et al 1995), and is indicative of oligotrophic conditions, as Dickinson et al (2002) recorded for Roaring Lion mire, which nutrient analysis indicated was minerotrophic to marginally ombrotrophic. In shallow depressions, Sphagnum falcatulum occurs (Vegetation type V), a species which is normally confined to hollows and shallow pools (Burrows 1969;Dobson 1979), or domed mires (McQueen & Wilson 2000), indicating tolerance of extremely low nutrient levels. Mark et al (1995) found Isolepis aucklandica also typical of pools on the Garvie Mountain aapa mires, though it is unimportant in pools here, instead being more common on pool margins and other drier sites (Vegetation types E, G, Q, R, T).…”
Section: Mire Vegetationmentioning
confidence: 99%
See 1 more Smart Citation